MECHANISM FOR THE FORMATION OF PEDAGOGICAL SKILLS OF FUTURE PHYSICAL EDUCATION TEACHERS THROUGH RHYTHMICAL GYMNASTICS TRAINING (Proximus Journal of Sports Science and Physical Education, 2025)
This article highlights the mechanism for the formation of pedagogical skills of future physical education teachers based on rhythmic gymnastics classes. During the study, experimental work was carried out with the participation of 2nd-year students of the Physical Culture program of Fergana State University. Based on analytical analysis, the theoretical, practical, and methodological aspects of rhythmic gymnastics were studied, and its positive influence on pedagogical training was substantiated. The mechanism put forward in the article has proven to be an effective tool for the development of professional competencies of future teachers and provides practical recommendations.